(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This article discusses the border dispute between Afghanistan and Pakistan, the Durand line. The article also discusses in detail the factors that led to the creation of this line, in particular the geopolitical and economic reasons.